Effects of topical combinations of clonidine and pentoxifylline on capsaicin-induced allodynia and postcapsaicin tourniquet-induced pain in healthy volunteers: a double-blind, randomized, controlled study. Issue 10 (October 2016) - Ragavendran, J. Vaigunda; Laferrière, André; Bennett, Gary J.; Ware, Mark A.; Gandhi, Wiebke; Bley, Keith; Schweinhardt, Petra; Coderre, Terence J.
Abstract : Abstract: This double-blind randomized controlled study was designed to evaluate the analgesic effects of topical treatments with clonidine (CLON) and pentoxifylline (PTX) tested alone or as low- and high-dose combinations in a human experimental model of pain. Of 69 healthy subjects aged 18 to 60 years, 23 each were randomly allocated to low-dose (0.04% + 2%) and high-dose (0.1% + 5%) CLON + PTX groups. Both of these groups also received their corresponding placebos in one of 2 treatment periods separated by at least 48 hours. Twenty-three additional subjects received either CLON (0.1%) or PTX (5%) as single drug treatments, in each of 2 treatment periods. Assessment of analgesic efficacy was based on allodynic effects of previous intraepidermal capsaicin injection, as well as postcapsaicin tourniquet-induced pain 50 minutes following capsaicin injection. Visual Analogue Scale (VAS) ratings of pain intensity and the area of dynamic mechanical allodynia were the primary outcome measures, whereas area of punctate mechanical allodynia (PMA) served as a secondary outcome measure. Topical treatments with high- or low-dose combinations significantly reduced VAS ratings compared with corresponding placebo treatments throughout the period of postcapsaicin tourniquet-induced pain. Importantly, the high-dose combination produced lower VAS ratings than CLON alone, which were lower than PTX alone. Results also revealed significant inhibition of postcapsaicin dynamic mechanical allodynia and PMA for the high-dose combination compared with placebo, and of PMA for CLON compared with the low-dose combination. Hence, the present data are supportive of further clinical investigation of the high-dose topical combination of CLON + PTX in complex regional pain syndrome and neuropathic pain patients, for which our preclinical data predict efficacy. Abstract : Supplemental Digital Content is Available in the Text.Topical combination of clonidine and pentoxifylline, more effectively than single agents alone, alleviates postcapsaicin tourniquet-induced pain, as well as capsaicin-induced allodynia, in healthy human volunteers.